Central screw use delays implant dislodgement in osteopenic bone but not synthetic surrogates: A comparison of reverse total shoulder models. (27th August 2019) - Hast, Michael W.; Chin, Matthew; Schmidt, Elaine C.; Kuntz, Andrew F.
Abstract: Adequate glenoid baseplate fixation in reverse total shoulder arthroplasty (rTSA) is important to achieve, but may prove challenging in the context of glenoid bone loss or osteopenia. Current rTSA testing standards rely upon synthetic bone surrogates, but it is unclear if these models accurately recapitulate the mechanics of osteoporotic bone. Additionally, it also unknown if the use of a central screw effectively provides resistance to micromotion in the milieu of poor quality bone. The purpose of this experiment was to create a novel cyclic load test protocol that elicited clinically relevant failures, so that comparisons of relative motion between baseplates and bones could be made with: (1) synthetic bones and poor quality cadaveric bones, and (2) the use or omission of a central screw. rTSA components were implanted into cadaveric and synthetic bones with and without a central screw. To model a range of loads that may be experienced during abduction, increasing cyclic loads were applied to shoulder joints in 30° of humeral abduction. Cycles and loads prior to permanent deformation exceeding 150 µm, 1 mm, and joint failure were determined using measurements from the test frame and from 3-D motion analysis. Synthetic bones demonstrated significantly more resistance to micromotion in comparison to cadaveric bones. Use of the central screw improved resistance to dislodgement, which was only observed in the cadaveric specimens. This study highlights the need for biomechanical testing with cadaveric specimens, especially when assessing osteopenic or osteoporotic populations.